Microsurgical Transcranial Approach of 112 Paraoptic Meningiomas: A Single-Center Case Series. Issue 6 (10th July 2020) - Lefevre, Etienne; Terrier, Louis-Marie; Bekaert, Olivier; Simonneau, Adrien; Rogers, Alister; Vignal-Clermont, Catherine; Boissonnet, Hervé; Robert, Gilles; Lot, Guillaume; Chauvet, Dorian
Abstract: BACKGROUND: Predictors of visual outcomes after optic nerve decompression are controversial. OBJECTIVE: To identify the predictors of poor visual outcomes after surgery of meningiomas responsible of a compressive optic neuropathy. METHODS: We focused on paraoptic meningiomas (POMs), which gathered tuberculum sellae meningiomas (TSMs) and anterior clinoid meningiomas (ACMs) responsible for visual impairment or threatening visual function, that underwent surgery at our institution between January 2009 and December 2015 and analyzed the clinical and radiological findings of our patients. RESULTS: Among 112 patients who underwent surgery for a POM, a preoperative visual deficit was present in 108 patients (96.4%). Six months after surgery, 79 patients (70.5%) had a visual improvement, 15 patients (13.4%) had an unchanged vision, and 18 patients (16.1%) had deteriorated vision. A preoperative visual deficit of 6 mo or more was a strong predictor of poor visual outcome after surgery ( P = .034). Poor visual outcome after surgery was not significantly related to the size of the tumor ( P = .057), the age of the patient ( P = .94), or the tumor extension into the optic canal ( P = .47). CONCLUSION: The duration of preoperative visual deficit was found to be a strong predictor of poor visual outcomes after surgery in POMs Other predictors of poor visual outcomes are still needed and are currently under evaluation in a prospective study at our institution. Graphical Abstract: